Systemic Chemotherapy Including Ramucirumab in Combination With Pressurized Intra-Peritoneal Aerosol Chemotherapy Is a Safe Treatment Option for Peritoneal Metastasis of Gastric Cancer - Feldbrügge, Linda; Gronau, Felix; Brandl, Andreas; Auer, Timo Alexander; Oeff, Alan; Thuss-Patience, Peter; Pratschke, Johann; Rau, Beate (Frontiers in Oncology, 2021)
Background. Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is a laparoscopic technique for local chemotherapy. It has been used for treatment of peritoneal metastasis of gastric cancer (PM GC) in combination with systemic therapy. VEGFR2 antagonist ramucirumab is a second-line therapy for GC, and has been suspected to cause wound healing disorders. Methods. This is a retrospective single center cohort study of patients with PM GC, who received PIPAC treatment in combination with systemic chemotherapy with and without ramucirumab. Data on patients’ characteristics and their perioperative courses were collected and complication rates were compared with regard to preoperative use of ramucirumab and time between last dose of systemic therapy and PIPAC treatment. Results. Fifty patients underwent 90 PIPAC treatments for PM GC in three years. Overall postoperative morbidity was 11% with 6% severe complications. The mean interval between systemic therapy and PIPAC was 20 days. Neither the length of interval nor the use of ramucirumab had an effect on complication rates. Conclusion. Our study suggests that addition of ramucirumab to pre-PIPAC systemic therapy, irrespective of the length of the treatment-free interval before PIPAC, does not increase the risk of postoperative complications and is therefore a safe option for treatment of PM GC.